2017
DOI: 10.1021/acs.chemmater.7b01595
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Tuning of Carrier Type and Concentration in a Homologous Series of Crystalline Chalcogenides

Abstract: Tellurium-based phase-change materials (PCMs) enable applications from optical and electronic data storage to thermoelectrics and plasmonics, which all demand precise control of electronic properties. These materials contain an unusually large number of vacancies: "stoichiometric" ones that stem from the chemical composition and "excess" vacancies that act like classical dopants. Here we show how both types of vacancies can be controlled independently in the solid solution Sn(Sb 1−x Bi x ) 2 Te 4 . We vary x i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 64 publications
0
24
0
Order By: Relevance
“…Moreover, it is known that the epitaxial films are strongly p-type doped [35] with an unintentionally varying charge carrier density p = (0.1-3) × 10 26 m −3 [24,26]. This doping is typically related to excess vacancies [36][37][38]. The epitaxial films also exhibit a significantly improved mobility μ with respect to polycrystalline films prepared by magnetron sputtering, i.e., an increase of μ by more than an order of magnitude [24,26,39].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is known that the epitaxial films are strongly p-type doped [35] with an unintentionally varying charge carrier density p = (0.1-3) × 10 26 m −3 [24,26]. This doping is typically related to excess vacancies [36][37][38]. The epitaxial films also exhibit a significantly improved mobility μ with respect to polycrystalline films prepared by magnetron sputtering, i.e., an increase of μ by more than an order of magnitude [24,26,39].…”
Section: Introductionmentioning
confidence: 99%
“…This already pointed to a prominent role of disorder. The number of charge carriers, on the contrary, was rather firmly linked to the number of (excess) vacancies, but hardly changed during annealing, thus not contributing significantly to the conductivity trend.…”
Section: Structural Length Scales Of Gst124 Samples Deposited At Varimentioning
confidence: 93%
“…Anderson localization in vacancy‐rich compounds was already investigated by Cutler and Mott in 1969, who showed that in Ce 2 S 3 , the random distribution of vacancies creates a tail of localized states in the conduction band, and that addition of a small number of cerium atoms per formula unit leads to a small number of electrons in the tail of the band and, thus, to insulating behavior. [ 31 ] More recently, Anderson localization effects were observed in rocksalt‐like compounds chemically related to the abovementioned PCMs, including SnBi 2 Te 4 and SnSb 2 Te 4 thin films, [ 32,33 ] and also in GeTe nanowires. [ 34 ] In ref.…”
Section: Figurementioning
confidence: 99%